Effectiveness of Interactive Video-Based Education on Improving Mental Health Literacy in Adolescents - Syifa Febrianti; Lia Juniarni; Purnama, Heni (LPPM UNIKAL, 2025)
Background: Teenagers are vulnerable to mental health problems due to emotional challenges, behavior, family problems, and social interactions in friendship and social environments. Being aware of mental health problems is indicated by high literacy. One effort to increase mental health literacy among teenagers is to package information to be very interesting through the use of interactive videos. Objective: This study aims to determine the effectiveness of interactive video-based education on improving mental health literacy in adolescents. Method: This research was quasy eksperimental design two-group pre-post test, where the number of respondents was 84 and divided into 42 intervention groups and 42 control groups. The inclusion criteria in this study were adolescents aged 15-18 years. The instruments used Mental Health Literacy Questionnaire (MHLQ). The data analysis used in this study was used Paired Sample T Test and ANCOVA. Results: The results showed that there was a significant difference in scores in the intervention group between pre-test and post-test (p = 0.000), while in the control group there was no significant difference between pre-test and post-test (p = 0.125). There was a significant effect with p-value = 0.000. Conclusion: Interactive videos presented by providing stimuli for more than one sense can have a positive impact on increasing literacy, especially regarding mental health. Suggestion: Further research can be carried out in developing applications that contain interactive video content in them.